Switching the horizontal GRF to the path of progession in the table tennis forehand drive - Chen, Y. -Y.; Hsueh, Y. C.; Tsai, C. -L. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Knowing the kinetic strategies of the lower limbs is a crucial factor to investigate the forehand drive which comprises the changes of the foot placement. It is difficult to directly evaluate the movement of feet with the data of ground reaction force (GRF) and impulse (GRI).This study tried to analyze table tennis forehand drives via the GRF and GRI data based upon the anatomical perspective. The motion and the GRF data were collected from eight right-handed Taiwanese elite table tennis players. The horizontal GRF data were transformed to a reference frame and then integrated with time to get the GRI. During the forehand drive shot, the participants performed a greater lateral impulse to cause the trunk rotation and decelerated their body from initial to mid-phase and then accelerated the body to perform a forehand drive shot.